Regionalisation or Regionalism? The Contemporary Legal Status of Cooperation in the South Pacific - Siekiera, Joanna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
This article aims to analyse the legal status of regional cooperation among the South Pacific countries and territories, as not every entity in the Pacific Basin possesses International law features of a state. Regionalisation, as well as regionalism, as illustrated by the example of the South Pacific region, is a new topic to examine, especially in the Polish and European literature. Therefore, this topic does need further and deeper analysis. First of all, both regionalism and regionalisation are international phenomena that were set against the process of globalisation only in the last two decades of the 20th century. Secondly, the Pacific Ocean became more dominant in geopolitics than the Atlantic Community at the beginning of 21st century. There are many publications regarding local cooperation mechanisms worldwide. Most of them, though, concern political and/or economic integration, and neglect the legal aspects of regional integration. The outcome of this article is nonetheless to present the contemporary legal statusof the South Pacific cooperation, though it is at the stage of regionalisation, while not yet regionalism – fully formalised and structuralised just as it is on the other continents.